2015
DOI: 10.1177/000313481508100820
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Bariatric Surgery: Increasing the Economic Viability of the Most Effective Treatment for Type II Diabetes Mellitus

Abstract: There has been considerable debate on the cost-effectiveness of bariatric surgery within larger population groups. Despite the recognition that morbid obesity and its comorbidities are best treated surgically, insurance coverage is not universally available. One of the more costly comorbidities of obesity is Type II diabetes mellitus (T2DM). We propose a model that demonstrates the cost-effectiveness of increasing the number of bariatric surgical operations performed on patients with T2DM in the United States.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Fifty six percent ( n = 43) of studies' data is predominantly is sourced from or originated from the USA . Studies also originated from Sweden 10% ( n = 8), Australia 8% ( n = 6), UK 8% ( n = 6), Canada , and the remainder of the included studies each for France ( n = 2),Germany , (Austria, Italy, Spain) , Spain , Norway , Portugal , the Netherlands , Finland , South Korea , Brazil ( n = 2) and Mexico .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty six percent ( n = 43) of studies' data is predominantly is sourced from or originated from the USA . Studies also originated from Sweden 10% ( n = 8), Australia 8% ( n = 6), UK 8% ( n = 6), Canada , and the remainder of the included studies each for France ( n = 2),Germany , (Austria, Italy, Spain) , Spain , Norway , Portugal , the Netherlands , Finland , South Korea , Brazil ( n = 2) and Mexico .…”
Section: Resultsmentioning
confidence: 99%
“…Of those that reported a time horizon, 42% ( n = 32) adopted a timeframe of ≤5 years and 53% of these studies reported results for ≤2 years ( n = 17) (mostly cost and cost analyses). Some cost and cost analyses reported a longer time horizon of 6–10 years ( n = 12, 16%) or 11–20 years ( n = 3, 4%) . In these studies, there was a significant loss of participants to follow‐up in the later years for large samples or analyses were informed by a small sample from a single study centre .…”
Section: Resultsmentioning
confidence: 99%
“…If we take into account only the cost of treating type 2 diabetes mellitus in the obese population, we could expect direct 10-year aggregate cost savings of $2.7 million/1000 people. The indirect cost, which takes into account the cost paid by society in terms of loss of work productivity due to sick leave or disability, has been proposed at $5.4 million/1000 [ 24 ]. Moreover, others have estimated the indirect cost of obesity to cost our society $48 billion to $64 billion annually [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Roux-en-Y gastric bypass (RYGB) surgery is currently the most effective treatment for T2DM resulting in long-term remission in a proportion of patients [ 2 4 ]. Whilst considered cost-effective and safe, the availability of the operation is unable to meet the demand due to the rapidly rising prevalence of obesity [ 5 , 6 ]. Furthermore, although RYGB may result in improvement in obesity comorbidities, not all patients with diabetes undergo remission.…”
Section: Introductionmentioning
confidence: 99%